Vibration-driven SEI thinning and inorganic domination: Enhanced lithium-ion battery performance - Jaewon Ryu; Taeksoo Jung; Jinwook Jung; Sunghyun Jie; Bora Lee; Junho Suh; Byeongyong Lee (Applied Surface Science Advances, 2025)
The electrification of the transportation sector has led to the widespread deployment of lithium-ion batteries (LIBs) in vehicles. Given that vehicles operate under dynamic conditions where mechanical stimuli are prevalent, LIBs in this system can be significantly influenced by these mechanical effects. However, the influence of mechanical factors on batteries remains insufficiently explored. Among these, vibration—an intrinsic characteristic of vehicular operation—has received limited attention. In this study, we demonstrate that mechanical vibration can significantly enhance the electrochemical performance of standard LIBs by rendering a more favorable solid electrolyte interphase (SEI) for Li⁺ transport. Electroanalytical measurements and finite element analysis reveal that vibration-induced shear forces selectively remove fragile organic components from the SEI, yielding a thinner and more inorganic-rich interphase that facilitates efficient Li⁺ migration. As a result, Graphite‖NMC111 cells exhibited a 40.5 % increase in capacity at 1.5C under vibrating conditions. By uncovering the beneficial role of vibration, this work reframes it from a peripheral disturbance to a central design lever for improving LIB performance, especially in motion-intensive environments.